Machine Learning for Predictive Maintenance to Enhance Energy Efficiency in Industrial Operations - Cruz, Juan Carlos; Garcia, Antonio Miguel (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2024)
In the realm of industrial operations, optimizing energy usage is critical for both economic and environmental sustainability. Traditional approaches to maintenance often rely on fixed schedules or reactive responses to equipment failures, leading to inefficiencies and higher energy consumption. Predictive maintenance (PdM) offers a proactive solution by leveraging machine learning algorithms to predict equipment failures before they occur. This approach not only reduces downtime but also facilitates energy-efficient practices by enabling timely interventions and optimized operational strategies. This study explores the application of machine learning techniques for predictive maintenance in a manufacturing setting. Historical operational data, including equipment performance metrics and environmental conditions, are collected and preprocessed. Various machine learning models, such as support vector machines (SVM), random forests, and neural networks, are trained on this dataset to predict equipment failures and maintenance needs. Feature engineering and model selection processes are detailed to highlight the steps taken to enhance prediction accuracy and reliability. Through rigorous experimentation and validation, our approach demonstrates significant improvements in energy efficiency within industrial operations. By predicting maintenance needs in advance, downtime is minimized, and energy-intensive emergency repairs are avoided. Furthermore, the implementation of optimized maintenance schedules and operational strategies based on machine learning predictions leads to substantial reductions in overall energy consumption. Case studies and quantitative analyses underscore the efficacy of our methodology in enhancing both operational efficiency and energy sustainability in industrial settings.